1997
DOI: 10.1097/00124784-199705000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Health Performance in Iowaʼs Counties

Abstract: Local health agencies in Iowa were surveyed to assess the performance of public health practices in their communities. Responses were received from 97 percent of counties. Less than 50 percent of counties were performing half of the indicators of the Assessment function. Policy Development functions also were frequently not performed. Performance was best in the Assurance function, with 86 percent of counties reporting that they inform and educate the public. However, the other three types of Assurance practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Several studies have suggested that regionalization, or combining adjacent jurisdictions with smaller populations, could increase the capacity of rural LHDs (57,107,113). However, given that homogeneity with respect to geographic size, morbidity, and SES is important to maintain high performance of multicounty rural jurisdictions, this recommendation should be undertaken with caution (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that regionalization, or combining adjacent jurisdictions with smaller populations, could increase the capacity of rural LHDs (57,107,113). However, given that homogeneity with respect to geographic size, morbidity, and SES is important to maintain high performance of multicounty rural jurisdictions, this recommendation should be undertaken with caution (31).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a similar emphasis continues in Healthy People 2010 by ensuring that health agencies have the infrastructure to provide effectively the ten essential public health services (83). Several researchers have studied compliance with the objectives of Healthy People 2000 by developing surveys to measure how well LHDs provide the core functions of public health (34,52,53,65,66,70,78,80,81). The results from these studies strongly suggest that the LHDs surveyed were not completely fulfilling the core public health functions.…”
Section: Function-based Assessmentsmentioning
confidence: 99%
“…The Future of Public Health (1988) recommended that local public health agencies should "regularly and systematically collect, assemble, analyze, and make available information on the health of the community, including statistics on health status, community health needs, and epidemiologic and other studies of health problems [3]. However, even when assessments were completed, policy development and assurance mostly did not follow [4,5]. …”
Section: Introductionmentioning
confidence: 99%